PHYSICAL FITNESS VALUE OF STUDENTS OF PRIVATE JUNIOR HIGH SCHOOL BHAYANGKARI 2 KABANJAHE - Barus, Join Marshelindo; Ibrahim, Ibrahim (Journal of Physical Education, Health and Sports Recreation, 2023)
This study aims to determine the level of physical fitness of students at Private Middle School Bhayangkari 2 Kabanjahe. This research was conducted at the Samura sports stadium. Data collection was carried out in October. The method used in this research is descriptive method by conducting tests and measurements. The test used was the Indonesian Physical Fitness Test for Junior High Schools, aged 13-15 years with a total sample of 40 people whose determination was based on purposive sampling. The results of this study did not find a level of physical fitness Very Good or 0.00%, nor found a level of physical fitness Good or 0.00%, in the moderate category there were 11 students or 27.50%, in the Less category there were 27 students or 67.50 %, in the Less Once category there are 2 students or 5.00%. Overall, the physical fitness level of the students of SMP PRIVATE BHAYANGKARI 2 KABANJAHE is 12.23 in the less category.